Recent Advances in Metal Decorated Nanomaterials and Their Various Biological Applications: A Review - Yaqoob, Asim Ali; Ahmad, Hilal; Parveen, Tabassum; Ahmad, Akil; Oves, Mohammad; Ismail, Iqbal M. I.; Qari, Huda A.; Umar, Khalid; Mohamad Ibrahim, Mohamad Nasir (Frontiers in Chemistry, 2020)
Nowadays, nanoparticles (NPs) have received much more attention biological field applications due to their unique and attractive physico-chemical properties. Among different types of nanocomposites, metal and metal oxides supported nanomaterials have been showed significant role in therapeutics and medical science. The mechanisms related to the interaction of nanoparticles with animal and plants cells establish significant role to improve their activity in health and medical applications. Various attempts have been made to discuss the antibiotic resistance and antimicrobial of metal supported nanoparticles. Despite all developments, still there is need to their performance by overcome modern challenges. In this regard, the present review proclaims the role of various types metal-supported nanomaterials in different fields such as antibacterial, antifungal, anticancer etc. field. Based on the significant applications, it is expected that metal-supported nanomaterials are anticipated to create their outstanding performance not only in medical but also in other fields.